1997
DOI: 10.1111/j.1095-8339.1997.tb02256.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between chromosomal and morphological characters in subspecies of Ulex europaeus L. (Genisteae, Leguminosae) from the north-west of the Iberian Peninsula

Abstract: The two subspecies of Ulex mn$mus L. (subsp. eumpms and subsp. latebracteatus) are easily differentiated by the shape and size of their bracteoles, and by their chromosome number. However, in the north-west of the Iberian Peninsula, the areas of both subspecies are not clearly delimited, the shape of the bracteoles is intermediate and the width is close to the diagnostic limit. Thus, allocation of some specimens to either subspecies is diffcult. Recently, a controversy has arisen concerning the intrapopulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…europaeus resulted from three different genomes, which means that these two taxa have different phylogenetic origins. Furthermore, Cubas & Pardo (40) showed that U. europaeus ssp. europaeus and U. europaeus ssp.…”
Section: Evidence Of Reticulated Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…europaeus resulted from three different genomes, which means that these two taxa have different phylogenetic origins. Furthermore, Cubas & Pardo (40) showed that U. europaeus ssp. europaeus and U. europaeus ssp.…”
Section: Evidence Of Reticulated Evolutionmentioning
confidence: 99%
“…europaeus and U. europaeus ssp. latebracteatus have distinct morphological characters, which are maintained in sympatric populations, and argued that ploidy acts as an effective reproductive barrier (40). Therefore, they do not fit the biological nor the phylogenetic species concepts and should be assign as different species.…”
Section: Evidence Of Reticulated Evolutionmentioning
confidence: 99%
“…Desde su introducción, al sur de la ciudad de Bogotá se ha venido expandiendo, ocupando áreas que han sido previamente degradadas por pastoreo, agricultura y ganadería (Salamanca & Camargo 2002). En la fase inicial de invasión, los individuos de U. europaeus pueden dispersar sus semillas hasta 6 metros de distancia de sus parentales, pero a través del tiempo, la especie genera grandes masas que obstaculizan la dispersión de éstas, por ende, se produce la acumulación de semillas que pueden ser viables entre 30 y 40 años, logrando germinar como respuesta a disturbios que provocan claros o por el deceso de algunos individuos de la población (Cubas & Pardo 1997, Moss 1959, MacCarter & Gaynor 1981, Barrera-Cataño 2011, Beltrán 2012 Actualmente U. europaeus tiene una ocupación de más de 3000 hectáreas, principalmente entre los biomas de páramo, bosque alto-andino y andino poniendo en peligro la existencia de este tipo de sistemas, debido a sus características biológicas, la presencia de esta especie pone en riesgo a los sistemas vecinos ya que además de quemarse ella misma propicia la quema de los sistemas vecinos, siendo ésta su manera de expandirse en el territorio (Barrera-Cataño 2011). La principal estrategia utilizada hasta el momento ha sido el control manual con resultados muy alentadores, sobre todo cuando los niveles de invasión son altos.…”
Section: Formulación Y Alcance Del Problema De Investigaciónunclassified
“…La dificultad para eliminar la especie fue enfatizada por Moss (1959) ya que sus semillas son muy pequeñas, se encuentra un promedio hasta de 16.000 semillas/m 2 (Barrera-Cataño 2011). Se ha medido la distribución de las semillas, aproximadamente el 75% de todas las semillas son encontradas en los primeros 5cm del suelo y la hojarasca (Moss 1959, Ivens 1978, Zabkiewicz & Gaskin 1978, Cubas & Pardo 1997, Clements & DiTommaso 2010.…”
Section: Descripción De La Especieunclassified